ANALISIS PENGARUH PELATIHAN KONSTRUKSI TERHADAP PENINGKATAN KOMPETENSI TENAGA KERJA KONSTRUKSI - Asman, Hasbi; Siswosukarto, Suprapto; Pratiwi, Endita Prima Ari (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
The strategic issue confronting the Indonesian construction services sector is the low level of ownership of Construction Work Competency Certificates (SKKK). Construction workforce development policies are concentrated on enhancing the competence of the construction workforce through training, with the aim of enabling them to perform work effectively and efficiently. Every aspect and stage of construction training is crucial; therefore, it is imperative to assess the effectiveness of construction training. This research addresses the measurement of construction training effectiveness by identifying and evaluating the factors and indicators that influence its effectiveness. The object under examination is a vocational training program in construction at the Medan Vocational and Productivity Training Center, specifically focusing on surveyor and building drafter job positions. This research evaluates the outcomes of the training program and assesses the four levels of Kirkpatrick's model criteria: reaction, learning, behavior, and results to find out what factors affect the effectiveness of training in increase human resources in construction services. Quantitative descriptive research method with data collection by distributing questionnaires to alumni training participants and superiors. Statistical analysis was carried out to determine the effect of construction training on increasing the competence of the trainees. Meanwhile, an analysis of the level of effectiveness was carried out to determine the interpretation value of the factors and measurement indicators by Relative Importance Index (RII) method. The results revealed a significant impact of construction training on improvement the competence of the trainees. The categorical factors and indicators exhibited a level of influence on improving knowledge, skills, attitudes, and performance, as indicated by the reaction level producing an RII value of (88,29%), learning (87,17%), behavior (88,75%), and results (87,19%). Precondition factors and indicators should be taken into consideration to ensure that the training yields effective results. Concepts related to the types of training and the factors that enhance training effectiveness necessitate robust decisions to steer the behavior and performance of trainees in a more favorable direction.